THE EFFECT OF QUALITY SERVICE ON CLIENT SATISFACTION AND LOYALTY IN TAX AND MANAGEMENT CONSULTANT OFFICE - Suyono Suyono; Ferri Firnando; Rangga Rahmadian Yuliendi; Sudarno Sudarno; Novita Yulia Putri (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of this study was to find out, test and analyze the effect of service quality on the satisfaction and loyalty of clients of tax and management consultant office Dr. Sudarno, S.Pd., M.M., BKP and colleagues Pekanbaru. The study was conducted at the office of tax and management consultant Dr. Sudarno Pekanbaru. The study time starts in August and until November 2021. Respondents in this study were taken from the client office of tax and management consultant Dr. Sudarno Pekanbaru, which is as many as 86 clients consisting of WPOP and WPB. The sampling techniques used in the study used saturated samples in which all members of the population were sampled. The number of samples used in the study was that all members of the study object population were 86 respondents. The data analysis techniques in this study used descriptive analysis the help of SPSS version 21 software. The results showed (1) Assurance has had a significant positive impact on client satisfaction (2) reliability, responsiveness, empathy, and tangibles have not had a significant positive impact on client satisfaction. Tangibles and satisfaction have a significant positive impact on client loyalty. (4) Reliability, responsiveness, assurance and empathy have not had a significant positive impact on client loyalty.